Embedded TCP/IP in sensor nodes (sensornets) - Mat Jubadi, Warsuzarina (2005)
A sensor network is a group of sensor nodes (sensor) which are connected and communicate each other. Sensor node has the ability to sense environmental data such as humidity, light, weight, and temperature, and has been ported with embedded TCP/IP protocol to perform the networking. A sensor node is equipped with a small micro controller, a radio transceiver, and an energy source. Sensors are constrained in terms of memory and processing power because of their limited physical size and cost. These constraints have been considered too limiting for physical size sensor to be able to use the TCP/IP protocols. This project was carried out to develop two sensor nodes that able to sense the temperature value, to embed the TCP/IP stack into the sensor nodes, and to apply the SLIP protocol into the TCP/IP stack. One will be the transmitter node while the other is the receiver node. The programming was developed with WinA VR, an A VR-GCC development tools and the hex code was ported using A VRISP connector. Finally, the transmission of data between sensor nodes is measured and result is compared between wired and wireless data.